PEDAGOGICAL AND PSYCHOLOGICAL FOUNDATIONS OF TEACHING ARCHITECTURAL DRAWING IN THE EDUCATION SYSTEM (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
: The article addresses the significant issues in understanding the teaching of architectural drawing and the methods for resolving them in student education.